Methodology for Analyzing Powder-Based Fire Extinguishing and Its Optimization - Amir Shalel; David Katoshevski; Tali Bar-Kohany (Fire)
Powder-based fire extinguishing methods are widely used to suppress fires of all kinds efficiently. However, these methods have several drawbacks, the most significant being the large powder residue left behind, which can complicate cleanup and damage sensitive equipment. The present paper investigates reacting flows and develops a methodology for analyzing the interaction of powder particles with fire, addressing both homogeneous and heterogeneous fire inhibition mechanisms. To achieve this, a simplified model was developed using the common principles of the general dynamic equation (GDE) and the population balance equation (PBE) coupled with the reacting flow equations. The model examines the interplay between the initial particles’ diameter and their extinguishing flow rate (concentration), also known as minimal extinguishing concentration (MEC), establishing the relation between the two. Notably, the relation exhibits three different zones, each influenced by different governing mechanisms of combustion inhibition, providing critical insights into optimizing powder-based extinguishing systems. A minimal value of the MEC is found where there is no significant change with the MEC in terms of particle diameter, and the chemical homogeneous mechanism is dominating. The methodology also offers a pathway for finding the maximal extinguishing particle diameter (MED) when the heterogeneous extinguishing mechanism acquires its maximal impact.There is no benefit with a larger particle diameter as it would not practically achieve better extinguishment, but would lead to a potential waste of powder and hence damage equipment. A significant advantage of using extinguishing powders with micro-sized/ultrafine particles is demonstrated where the homogeneous inhibition mechanism becomes predominant. The developed methodology and finding suggest that micro-sized powders are more effective in extinguishing fires, as they offer improved dispersion and reactivity, enhancing the overall efficiency of the fire suppression process. However, considering economic factors such as micron-sized-powder production cost and maintenance may require considering a shift of this set point.